Clinical Features and Risk Factors of Severe Pneumonia in Children With Acute Lymphoblastic Leukemia - Liu, Chun-yan; Li, Cheng (Frontiers in Pediatrics, 2022)
Objective This study aims to analyze the clinical characteristics of pediatric acute lymphoblastic leukemia (ALL) complicated by pneumonia and the risk factors of severe cases to preliminarily construct a prediction model for ALL complicated by severe pneumonia. Methods A retrospective analysis was carried out on the clinical data of children diagnosed with ALL complicated by pneumonia hospitalized at the Department of Pediatrics of the Affiliated Hospital of Southwest Medical University between January 2013 and December 2020. The risk factors of severe ALL complicated by pneumonia were investigated with logistic regression analysis, and the risk prediction model was constructed. Results A total of 116 cases of pediatric ALL complicated by pneumonia were analyzed. There were 71 cases of mild pneumonia and 45 cases of severe pneumonia. The main clinical manifestations were cough in 112 cases and fever in 109. Pathogens were detected in 23 cases. Multiple regression factor analysis indicated that the use of hormones (OR 4.001, 95% CI: 1.505–10.632), neutropenia or agranulocytosis (OR 7.472, 95% CI: 2.710–20.602), hemoglobin (Hb) < 90 g/L (OR 3.270, 95% CI: 1.256~8.516), and C-reactive protein (CRP) >15 mg/L (OR 3.253, 95% CI: 1.209~8.751) were independent risk factors that were associated with severe pneumonia. Logistic regression was used to establish the risk prediction model of ALL with severe pneumonia. The p-value was 0.659. The area under the receiver operating characteristic curve was 0.851, and the sensitivity and specificity were 84.4 and 71.8%, respectively. Conclusion The development of severe pneumonia may be affected by the use of hormones, neutropenia or agranulocytosis, Hb < 90 g/L, and CRP > 15 mg/L. The prediction model based on the risk factors is effective, which can provide a reference for the clinical evaluation of acute lymphoblastic leukemia with severe pneumonia.